De compras para la salud: Cereales de desayuno - Jenna Seckar; Wendy J. Dahl (EDIS, 2016)
It is no secret that breakfast is an important meal. Eating breakfast provides you with physical and mental energy to start the day, along with vitamins and minerals. Cereal is a quick, versatile, and budget-friendly breakfast choice. The benefits of eating a healthy cereal include increased fiber intake and lower body weight. But navigating the cereal aisle at your local grocery store can be an overwhelming experience. This 3-page fact sheet is the Spanish-language version of FSHN15-11/FS274: Shopping for Health: Breakfast Cereals. Written by Jenna Seckar and Wendy J. Dahl, and published by the Food Science and Human Nutrition Department, May 2016.